A comparative study on Light Gauge Member and Castellated Beam - v, vanathi; Venkatraman; B. Gokul Balaji (International Journal of Sustainable Construction Engineering and Technology, 2022)
Abstract: This research paper examines the comparative study on strength characteristics of a Cold rolled steel with castellated beam under the lateral distortional and torsional buckling modes. For studying a beam element, a STADD model is built. In the examination of cold-formed steel sections, material nonlinearity and geometric imperfection were taken into account. Variations in length and cross-section of a finite element model were investigated. For cold-formed steel sections and castellated beams, the load-deflection curve is plotted and examined. To investigate the strength and behavior of castellated steel beams, finite element modeling was used to modify the cross-section. The study shows that the web distortional buckling has been greatly influenced by the failure load in a castellated steel beams. The failure load of the beam is influenced by the steel strength; the higher the steel strength, the higher the failure load. The high-strength castellated steel beam fails due to local flange buckling, whereas the regular castellated steel beam fails due to lateral-torsional buckling in the web.